2016
DOI: 10.1152/japplphysiol.00561.2016
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy at high altitude in the Andes leads to increased total vessel density in healthy newborns

Abstract: The developing human fetus is able to cope with the physiological reduction in oxygen supply occurring in utero. However, it is not known if microvascularization of the fetus is augmented when pregnancy occurs at high altitude. Fifty-three healthy term newborns in Puno, Peru (3,840 m) were compared with sea-level controls. Pre- and postductal arterial oxygen saturation (SpO2) was determined. Cerebral and calf muscle regional tissue oxygenation was measured using near infrared spectroscopy (NIRS). Skin microcir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 43 publications
(53 reference statements)
0
19
0
Order By: Relevance
“…Niermeyer and colleagues found that [Hb] in Tibetan newborns was lower compared with Han Chinese newborns . There was no difference in [Hb] in Puno (3840 m) between newborn indigenous Aymaras, Hispanic, and mixed origin people . [Hb] increased linearly in Quechua boys by approximately 2.7 g/dL between the age of 6 and 21 years, which is in the same range as found in Caucasian boys and similar to the age‐related increase of Tibetan and Han Chinese children .…”
Section: Discussionmentioning
confidence: 61%
“…Niermeyer and colleagues found that [Hb] in Tibetan newborns was lower compared with Han Chinese newborns . There was no difference in [Hb] in Puno (3840 m) between newborn indigenous Aymaras, Hispanic, and mixed origin people . [Hb] increased linearly in Quechua boys by approximately 2.7 g/dL between the age of 6 and 21 years, which is in the same range as found in Caucasian boys and similar to the age‐related increase of Tibetan and Han Chinese children .…”
Section: Discussionmentioning
confidence: 61%
“…Angiogenesis is one of the key mechanisms of high-altitude adaptation [ 36 , 37 ]. Remarkably, FGF2 (fibroblast growth factor 2) ( di value = 10.53), one of the fibroblast growth factor family members ( FGFs) [ 38 ], has been proved as an angiogenic growth factor [ 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…In 2009, an international multicenter observational prevalence study in intensive care patients involving 36 ICUs worldwide enrolling 501 patients identified microcirculatory alterations (microvascular flow index, MFI < 2.6) in combination with tachycardia (heart rate > 90) as an independent risk factor for increased hospital mortality [28]. Various studies have been undertaken to define normal values in adults, newborns, and neonates [29][30][31][32][33], as well as in healthy individuals under extreme environmental conditions [34,35]. In studies where systemic hemodynamic monitoring was being applied, it became increasingly clear that microcirculatory alterations can occur independently from systemic hemodynamic alterations and that these microcirculatory alterations were independently associated with adverse clinical outcome [6][7][8].…”
Section: Introductionmentioning
confidence: 99%